In vivo Neuroregeneration to Treat Ischemic Stroke Through NeuroD1 AAV-Based Gene Therapy in Adult Non-human Primates - Ge, Long-Jiao; Yang, Fu-Han; Li, Wen; Wang, Tao; Lin, Yu; Feng, Jie; Chen, Nan-Hui; Jiang, Min; Wang, Jian-Hong; Hu, Xin-Tian; Chen, Gong (Frontiers in Cell and Developmental Biology, 2020)
Stroke may cause severe death and disability but many clinical trials have failed in the past, partially because the lack of an effective method to regenerate new neurons after stroke. In this study, we report an in vivo neural regeneration approach through AAV NeuroD1-based gene therapy to repair damaged brains after ischemic stroke in adult non-human primates (NHPs). We demonstrate that ectopic expression of a neural transcription factor NeuroD1 in the reactive astrocytes after monkey cortical stroke can convert 90% of the infected astrocytes into neurons. Interestingly, astrocytes are not depleted in the NeuroD1-converted areas, consistent with the proliferative capability of astrocytes. Following ischemic stroke in monkey cortex, the NeuroD1-mediated astrocyte-to-neuron (AtN) conversion significantly increased local neuronal density, reduced microglia and macrophage, and surprisingly protected parvalbumin interneurons in the converted areas. Furthermore, the NeuroD1 gene therapy showed a broad time window in AtN conversion, from 10 to 30 days following ischemic stroke. The cortical astrocyte-converted neurons showed Tbr1+ cortical neuron identity, similar to our earlier findings in rodent animal models. Unexpectedly, NeuroD1 expression in converted neurons showed a significant decrease after 6 months of viral infection, indicating a downregulation of NeuroD1 after neuronal maturation in adult NHPs. These results suggest that in vivo cell conversion through NeuroD1-based gene therapy may be an effective approach to regenerate new neurons for tissue repair in adult primate brains.